Prediction and Explanation of the Sense of Happiness and Hope for the Future Based on Parental Attachment Styles - Hosseini Harandehi, Seyedeh Fatemeh; Sedaghati Fard, Mojtaba (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The aim of this study was to predict and explain happiness and hope for the future based on parental attachment styles among female university students. Methods and Materials: This research was conducted using a descriptive-analytical and correlational design with a predictive approach. The statistical population included all female students of the Islamic Azad University, Garmsar Branch, during the academic year 2022–2023. A total of 274 students were selected using stratified and purposive sampling methods based on specific inclusion and exclusion criteria. Data were collected using the Oxford Happiness Questionnaire, Snyder’s Hope Scale, and Hazan and Shaver’s Adult Attachment Style Questionnaire. After obtaining informed consent, the data were analyzed through Pearson correlation, multiple regression, and path analysis using SPSS and AMOS software. Statistical significance was set at p < .05. Findings: The results showed that secure attachment style significantly and positively predicted both happiness (β = .38, p < .01; R² = .24) and hope for the future (β = .44, p < .01; R² = .31). Avoidant attachment style was a significant negative predictor of happiness (β = –.29, p < .01) and had a weaker, yet still significant, inverse relationship with hope for the future (β = –.11, p < .01). Ambivalent attachment style negatively and significantly predicted both happiness (β = –.17, p < .01) and hope for the future (β = –.30, p < .01). All regression models met the assumptions of normality, linearity, and independence of residuals. Conclusion: The findings suggest that parental attachment styles, particularly secure attachment, play a meaningful role in promoting positive psychological outcomes such as happiness and hope in emerging adults. Insecure attachment styles, including avoidant and ambivalent, are associated with diminished emotional well-being.